2011
DOI: 10.1099/jmm.0.031575-0
|View full text |Cite
|
Sign up to set email alerts
|

Host serum factor triggers germination of Clostridium perfringens spores lacking the cortex hydrolysis machinery

Abstract: Clostridium perfringens type A is the causative agent of a variety of histotoxic and enteric diseases. The ability of C. perfringens spores to germinate in vivo might be due to the presence of nutrient germinants in the host tissue and blood. In the current study, we investigated the ability of spores of C. perfringens wild-type and mutation strains to germinate in blood. Results indicate that spores of all three surveyed C. perfringens wild-type isolates germinated better in blood than in brain heart infusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
8
0
1
Order By: Relevance
“…Since a previous report (21) indicated that C. perfringens strain 13 has a frameshift mutation in the gene of the master regulator, spo0A (22,23), we examined the ability of spore formation of strain 13 under the same conditions as those used for SM101. As expected, strain 13 did not form spores (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Since a previous report (21) indicated that C. perfringens strain 13 has a frameshift mutation in the gene of the master regulator, spo0A (22,23), we examined the ability of spore formation of strain 13 under the same conditions as those used for SM101. As expected, strain 13 did not form spores (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…The composition and function of the spore coat in C. perfringens has not yet been carefully studied; however, in other Gram-positive spore formers, the spore coat is thought to be comprised of >50 spore-specific proteins and provides protection to the spore from reactive chemicals and lytic enzymes (12-14). In C. perfringens , a small fraction of the spore population (∼5%) is defective in spore coats (15). Those spores are permeable to lysozyme (15) so they can germinate inside the host under specific conditions.…”
Section: The Ultrastructure Of C Perfringens Sporesmentioning
confidence: 99%
“…In C. perfringens , a small fraction of the spore population (∼5%) is defective in spore coats (15). Those spores are permeable to lysozyme (15) so they can germinate inside the host under specific conditions.…”
Section: The Ultrastructure Of C Perfringens Sporesmentioning
confidence: 99%
See 1 more Smart Citation
“…(11)(12)(13) Os meios de cultivo mais usados para o isolamento de C. perfringens são o ágar Sulfito Polimixina Sulfadiazina (SPS) e o ágar Triptose Sulfito Cicloserina (TSC). (14) De acordo com a Agência Nacional de Vigilância Sanitária, a toxinfecção alimentar por C. perfringens é a sexta mais frequente no Brasil, entretanto, deve-se notar que em 51,34% de todos os casos de toxinfecção alimentar o agente causador é ignorado.…”
Section: Introductionunclassified